PENGARUH SALES GROWTH, KEPEMILIKAN MANAJERIAL DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL - Silvia Sari; Azzahraasyaida, Azzahraasyaida (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to analyze the effect of sales growth, managerial ownership, and on the capital. This research was conducted by analyzing the financial statements of companies in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2022. The sample used in this study was 24 property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022 using a purposive sampling technique. The data used in this study is secondary data in the form of financial reports from each company that has been used as a research sample. Panel data regression methode is used as a research methodology in this study. Analysis of research results using the help of Eviews. The results showed that the best model is the Fixed Effect Model (FEM). The results of this study indicate that sales growth, managerial ownership and asset structure simultaneously have effect on capital structure, and sales growth has no effect on capital structure, managerial ownership has an effect on capital structure and asset structure has no effect on capital structure.